Playing doctor : television, storytelling, and medical power - Turow, Joseph (University of Michigan Press, 2010)
"This book is a history of the medical TV series from its inception to the present day. Turow offers an inside look at the creation of iconic doctor shows as well as a detailed history of the programs, an analysis of changing public perceptions of doctors and medicine, and an insightful commentary on how medical dramas have both exploited and shaped these perceptions. This expanded edition includes a new introduction placing the book in the contemporary context of the health care crisis, as well as new chapters covering the intervening twenty years of television programming. Turow uses recent research and interviews with principals in contemporary television doctor shows such as ER, Grey's Anatomy, House, and Scrubs to illuminate the extraordinary ongoing cultural influence of medical shows."--Publisher.